THE PARTICIPATION OF THE LOCAL COMMUNITY IN THE HERITAGE PRESERVATION - Christina Banjarnahor, Susy (Akademi Pariwisata Darma Agung, 2024)
The utilization of heritage buildings in downtown Medan's Kesawan area has become a prime tourist attraction developed by the Medan City Government. Sustainable preservation of cultural heritage is crucial due to its significant benefits for the local community. Before the government's development, Kesawan appeared rundown with many abandoned, vandalized buildings and homeless people occupying them. Qualitative research gathered information through observation, literature study, and interviews with residents, government officials, heritage experts, and site managers. The study found that the Medan city government and related departments did not comprehensively supervise heritage preservation. The Irritation Index (Irridex) theory revealed that the community felt euphoria, showing they were pleased with tourists. Using SWOT, Tosun's typology indicated that community participation was induced and passive, needing encouragement from the government, trusted representatives, and structured involvement.